A Theoretic Basis for IS? The Contribution of ANT - Underwood, Jim (Australasian Journal of Information Systems, 2002)
Representation is a key issue of IS design and operation that is often ignored. Actor-network theory (ANT), a semiotic theory of stakeholders, provides a way of dealing with representation. Combining aspects of ANT and Foucault's discourse theory allows us to include concepts as actors and promises a flexible and durable foundation for IS practice, but ANT itself indicates that the search for a purely theoretical foundation for IS is misguided.